2013
DOI: 10.1111/pce.12238
|View full text |Cite
|
Sign up to set email alerts
|

Day length dependent restructuring of the leaf transcriptome and metabolome in potato genotypes with contrasting tuberization phenotypes

Abstract: Recent advances have defined some of the components of photoperiodic signalling that lead to tuberization in potato including orthologues of FLOWERING LOCUS T (StSP6A) and CYCLING DOF FACTOR (StCDF1). The aim of the current study is to investigate the molecular basis of permissive tuber initiation under long days in Solanum tuberosum Neo-Tuberosum by comparative analysis with an obligate short-day S. tuberosum ssp. Andigena accession. We show that the Neo-Tuberosum accession, but not the Andigena, contains all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 48 publications
(83 reference statements)
4
28
0
Order By: Relevance
“…Overexpression of the early-maturing/ tuberizing StCDF1.2 gene variant in the photoperioddependent potato subspecies andigena produced tubers under noninductive LD and also resulted in early tuber formation in a late-maturing line (Kloosterman et al, 2013). Consistent with these results, Morris et al (2014) reported that a Neo-Tuberosum accession adapted to tuberization in LD, but not the andigena subspecies, contained an allele that encoded for a truncated StCDF1 protein modified in the C-terminal region (similar to StCDF1.2). These genetic analyses confirm an important role of StCDF1 in controlling the timing of tuber formation.…”
Section: Identification Of Cdf1 Alleles In Potatosupporting
confidence: 76%
“…Overexpression of the early-maturing/ tuberizing StCDF1.2 gene variant in the photoperioddependent potato subspecies andigena produced tubers under noninductive LD and also resulted in early tuber formation in a late-maturing line (Kloosterman et al, 2013). Consistent with these results, Morris et al (2014) reported that a Neo-Tuberosum accession adapted to tuberization in LD, but not the andigena subspecies, contained an allele that encoded for a truncated StCDF1 protein modified in the C-terminal region (similar to StCDF1.2). These genetic analyses confirm an important role of StCDF1 in controlling the timing of tuber formation.…”
Section: Identification Of Cdf1 Alleles In Potatosupporting
confidence: 76%
“…As of March, 2017, the original publication of the DM sequence has been cited more than 500 times, providing a framework for studies of gene families (Charfeddine et al 2015;Gao et al 2016;Ma et al 2016;Schreiber et al 2014;Seo et al 2016;Tang et al 2016;Van Harsselaar et al 2017), a scaffold for alignment of transcriptomic data (Campbell et al 2014;Gong et al 2015;Goyer et al 2015;Liu et al 2015;Morris et al 2014;Tang et al 2014) or a reference genome against which to discover genomic variation (Hardigan et al 2016), to cite just a few. As sequencing platforms improve, the DM assembly will likely be supplanted by that of a more robust commercial potato line.…”
Section: Resultsmentioning
confidence: 99%
“…We have integrated potato gene expression data from over 20 studies based on the Agilent JHI Solanum tuberosum 60 k v1 microarray (ArrayExpress ID: E‐MTAB‐1655) processed at the James Hutton Institute using standard Agilent recommended methodologies (Hancock et al ). The studies included 326 conditions derived from the following treatments: moderate heat‐stress (Hancock et al ), short‐ and long‐day growth regimes (Morris et al ), bruising (unpublished data), phosphorous growth regimes (unpublished data), acidity, Phytopthora infestans infection (Ali et al ) and β‐aminobutyric acid (BABA) (Bengtsson et al ), phosphite, abscisic acid (ABA), brassinosteroid and salicylic acid (SA) treatments (unpublished data). Different potato accessions and tissues (tuber, stem and leaf) were included.…”
Section: Methodsmentioning
confidence: 99%